Genital and extra-genital warts increase the risk of asymptomatic genital human papillomavirus infection in men. Issue 5 (20th May 2011) - Hernandez, Brenda Y; Shvetsov, Yurii B; Goodman, Marc T; Wilkens, Lynne R; Thompson, Pamela J; Zhu, Xuemei; Tom, James; Ning, Lily
Abstract : Objectives: To evaluate the relationship of warts in different parts of the body and the risk of asymptomatic genital human papillomavirus (HPV) infection in men. Methods: We examined the relationship of self-reported genital and extra-genital warts with the subsequent acquisition of asymptomatic genital HPV infection in a cohort of 331 adult men. Participants were followed at 2-month intervals for up to 4 years. Past and current presence of warts was queried at study entry. At each visit, the external genitals were sampled for HPV DNA testing. Results: Men who reported a history of genital warts, including current warts, were at increased risk of acquisition of asymptomatic HPV infection of the penis glans/corona, penis shaft and scrotum. The magnitude of these associations was greatest for HPV 6/11 infection. History of warts on the fingers, arms and trunk of the body was also associated with increased risk of genital HPV infection. Current presence of warts on the fingers and trunk specifically increased the risk of acquisition of HPV types not typically found on the genitals. Conclusions: Men with a history of warts on the genitals, fingers, arms and trunk may be at increased risk for acquisition of new genital HPV infections. Warts may provide an efficient reservoir for the transmission of virions to the genitals through auto-inoculation. The potential for the spread of HPV throughout the body through auto-inoculation has important implications for prevention and control of HPV infection.